Exploring the effects of real-time online cardiac telerehabilitation using wearable devices compared to gym-based cardiac exercise in people with a recent myocardial infarction: a randomised controlled trial - Mitropoulos, A.; Anifanti, M.; Koukouvou, G.; Ntovoli, A.; Alexandris, K.; Kouidi, E. (Frontiers in Cardiovascular Medicine, 2024)
Background Exercise-based cardiac rehabilitation (CR) is a non-pharmacological multidisciplinary programme for individuals after myocardial infarction (MI) that offers multiple health benefits. One of the greatest barriers to CR participation is the travel distance to the rehabilitation centre. Remotely monitored CR appears to be at least as effective in improving cardiovascular risk factors and exercise capacity as traditional centre-based CR. Nevertheless, the efficacy of remotely monitored CR in individuals with a recent MI has yet to be examined. Methods A total of 30 individuals (8 women, 22 men) after a recent (i.e., <4 weeks) MI were randomly allocated into two groups (online home-based and gym-based groups). Both groups underwent a 26-week CR programme three times per week. All patients performed baseline and 24-week follow-up measurements where peak oxygen uptake (VO2peak), mean daily steps, distance, and calories were assessed. Results The online group showed an improvement in mean daily steps (p < 0.05) and mean daily distance (p < 0.05) at 24 weeks compared to the gym-based group. The paired-sample t-test showed that all the assessed variables were statistically (p < 0.001) improved for both groups at 24 weeks. Pearson's r demonstrated positive correlations between VO2peak and mean daily distance (r = 0.375), and negative correlations between VO2peak and muscle (r = −0.523) and fat masses (r = −0.460). There were no exercise-induced adverse events during the study. Conclusion Our findings might indicate that a real-time online supervised CR exercise programme using wearable technology to monitor the haemodynamic responses in post-MI patients is equally effective as a gym-based exercise programme.